Design, Implementation and Advanced Control of a Push-Pull Power Converter - Bentourki Marouane; Lagmi Messaoud; BENMILOUD Mohammed (University of Amar Telidji - Laghouat Faculty of Technology Department of Electronics, 2023)
The purpose of this master project is to build a DC/DC power converter, known as push-pull power converter. The converter is widely used in photovoltaic systems which allows to increase the DC voltage by the mean of a set of switches, a transformer, rectifier and a filter. To guarantee a good operation of the converter, a linear quadratic regulator (LQR) is proposed which ensures the stabilization of the output voltage around a given reference. Simulation and experimental results show the effectiveness of the experimental setup and its control scheme under load and input voltage variations.
SPECIALTY: Automation & Industrial Computing